Perlindungan Tenaga Kerja Security Dengan Hak Kontrak Di Perusahaan Outsourcing Berdasarkan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Sri Ayu Astuti , Sri Ayu Astuti; Herizali Harahap , Herizali Harahap (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
The Outsourcing (outsourcing) as a provider of workers by another party is carried out first by separating the main work (core business) from supporting work (non-core business) in a written document prepared by company management. In outsourcing, companies using outsourcing services collaborate with outsourcing companies, where the legal relationship is manifested in a cooperation agreement which contains, among other things, the term of the agreement and what areas constitute a form of outsourcing cooperation. This research aims to determine the civil rights of outsourced workers, especially security workers after the enactment of Law Number 11 of 2020 concerning Job Creation. This type of research uses empirical normative juridical research methods. Data processing is presented using qualitative descriptive techniques and data collection is carried out through literature studies and interviews. The research results show that Law Number 11 of 2020 concerning Job Creation does not address the issue of protecting workers from violations of outsourcing practices that have occurred so far, such as violations of wage provisions, working hours and types of work that are outsourced.